Impact of elite soccer coaching change on team performance according to coach- and club-related variables - Gómez, Miguel A.; Lago-Peñas, Carlos; Gómez, María-Teresa; Jimenez, Sergio; S. Leicht, Anthony (Biology of Sport, 2021)
A coaching change is an extreme, but frequently occurring phenomenon in elite soccer with its impact on team success debatable. The aim of the current study was twofold: (i) to compare team’s performance when coached by new and old coaches; and (ii) to investigate the impact of a coaching change on team’s performance according to coach- and club-related factors. All in-season coaching changes from the 2010–11 to 2017–18 seasons within the Spanish, French, English, German and Italian professional leagues were examined. Team performance was assessed as points awarded from match outcome over 1–20 matches prior to and following the coaching change. Four independent variables (coach’s experience, team’s budget, whether the coach had been an elite former player or not, and whether the coach was a novice or not) were included into linear regression modelling. The main results showed that team’s short-term performance was improved significantly with a change to a new coach with this impact declining in the longer term (> 10 matches). Specifically, the number of points (1.15–1.32 vs. 0.37–1.03, p < 0.05) and the moving average of points (1.19–1.31 vs. 0.37–1.04, p < 0.05) awarded per match were significantly greater after the coaching change. Further, the winning effect due to the new coach was independent of coach-related factors such as coaching experience or the new coach being a former elite player. A critical organisational decision to change coaches may provide an essential stimulus for future team success in elite soccer.